Melatih Kecerdasan Visual-Spasial Siswa SMA dengan Scaffolding Berbantuan Media 3D - Kartika, Hendra; Firmansyah, Dani (EDUPEDIA Publisher, 2022)
Visual-spatial intelligence is one of the multiple intelligences possessed by each individual. This intelligence needs to be trained and developed in individuals because each individual has a different level of imagination and spatial sensitivity. In addition, there is a need for methods that can develop visual-spatial intelligence. One method that can be used is to provide problem solving exercises with scaffolding using 3-dimensional (3D) learning media. The method used in this activity is training with scaffolding assisted by 3D media. In this activity, students are given visual-spatial practice questions. The results of the activity showed that there was an increase in students' understanding of the importance of training visual-spatial intelligence for psychological activities for college entrance tests, work entrance tests, and so on.